EFFECT OF FRYING TEMPERATURE/FRYING CYCLES ON trans-FATS AND OXIDATIVE STABILITY OF GROUNDNUT OIL - CARDIAC RISK FACTORS - Jain, Akanksha; Passi, Santosh Jain; Selvamurthy, William; Singh, Archna (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Frying process leads to oxidative deterioration and generation of trans fatty acids (TFAs) in fats/oils resulting in elevated cardiac risk. The objective of this study was to assess the effect of frying temperatures and the number of frying cycles on TFA and primary/secondary oxidative indices of groundnut oil used for preparing French fries. Methods: TFA (by gas chromatography) and other chemical parameters (by American Oil Chemists' Society official methods) were estimated at varying temperatures (160°C, 180°C, 200°C, 220°C and 230°C) and frying cycles (1st, 4th, 8th 16th and 32nd). Results: With soaring frying temperatures and progressive frying cycles, mean cis-unsaturated fatty acids decreased while mean saturated fatty acids and TFA increased. Temperature variation indicated increase in mean TFA from 0.13±0.02 g/100 g (160°C; 32nd cycle) to 1.88±0.04 g/100g (230°C;32nd cycle) (p<0.05). With successive frying cycles, TFA increased from 0.10±0.01 g/100 g (1st cycle) to 0.13±0.02 g/100 g (32nd cycle) when oil was heated to 160°C; and 1.16±0.02 g/100 g (1st cycle) to 1.88±0.04 g/100 g (32nd cycle) when oil reached 230°C. Acid value, p-anisidine value and total oxidation value demonstrated a significant increase at varying frying temperatures across the frying cycles (p<0.05); however, peroxide value (PV) indicated an inconsistent trend. Conclusion: TFA and oxidative parameters increased with elevating frying temperatures and progressive frying cycles; however, PV demonstrated inconsistency. Food safety agencies need to formulate policies, stringent food laws and impose necessary regulations to curb oil abuse during frying. There is a dire need to raise consumer awareness regarding deleterious health effects of TFA and oxidative deterioration of edible oils.